MODL-12. A NOVEL GENETICALLY ENGINEERED H3.3G34R MODEL REVEALS COOPERATION WITH ATRX LOSS IN UPREGULATION OF HOXA CLUSTER GENES AND PROMOTION OF NEURONAL LINEAGE. (14th November 2022) - Abdallah, Aalaa; Cardona, Herminio; Gadd, Samantha; Brat, Daniel; Wadhwani, Nitin; Shen, Chen; Picketts, David; Li, Xiao-Nan; Becher, Oren
Abstract: BACKGROUND: Pediatric high-grade gliomas (pHGGs) are an aggressive CNS tumor which are often characterized by mutations in H3F3A, the gene that encodes Histone H3.3 (H3.3). A substitution of the Glycine at position 34 of H3.3 with either Arginine or Valine (H3.3G34R/V), was recently described in a large cohort of pHGG samples and has been characterized as occurring in anywhere between 5-20% of pHGGs. Attempts to study the mechanisms of H3.3G34R have proven difficult due to the developmental nature of the disease and the requirement of co-occurring mutations for model development. METHODS: We utilized the RCAS/tv-a system to develop a genetically engineered mouse model (GEMM) that incorporates PDGF-A activation, TP53 loss and the H3.3G34R mutation both in the context of ATRX loss and ATRX presence in nestin expressing progenitor cells. RESULTS: Transcriptomic analysis revealed that ATRX loss in the context of H3.3G34R upregulates the Hoxa cluster genes Hoxa2, Hoxa3, Hoxa5, and Hoxa7 (p < 0.05, unpaired t-test). H&E staining and EMA immune-staining indicate that ATRX loss is correlated with a higher incidence of ependymal differentiation in H3.3G34R expressing samples (p < 0.05, unpaired t-test). GSEA and RT-qPCR analysis demonstrate that H3.3G34R expression in the context of ATRX loss promotes increased expression in genes associated with neuronal lineage (FWER pval < 1.0) and exhibits upregulation of the neurofilament polypeptides Nefl, Nefm (p < 0.05, unpaired t-test) as well as the neuronal differentiation marker Stmn2 (p < 0.001, unpaired t-test). CONCLUSION: Our study proposes a model in which cooperation between ATRX loss and H3.3G34R expression mediate major transcriptomic and histopathological changes in H3.3G34R pHGGs. Broadly, our work highlights the importance to study mechanisms of co-occurring genetic events separately and in combination.